2009
DOI: 10.1038/jhh.2009.107
|View full text |Cite
|
Sign up to set email alerts
|

Aliskiren for Geriatric Lowering of Systolic Hypertension: a randomized controlled trial

Abstract: Efficacy and safety of the direct renin inhibitor aliskiren was compared with ramipril for treatment of essential systolic hypertension in elderly patients. A 36-week, randomized, double-blind, parallel-group, active-controlled, optional-titration study was performed in 901 patients (aliskiren, n ¼ 457; ramipril, n ¼ 444) X65 years of age with systolic blood pressure (SBP) X140 mm Hg. Aliskiren 150-300 mg per day or ramipril 5-10 mg per day for was administered for 12 weeks with optional add-on therapy of hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(94 citation statements)
references
References 35 publications
6
87
0
1
Order By: Relevance
“…For example, in the AGELESS study, aliskiren therapy was associated with a lesser incidence of adverse effects compared with ramipril (70% less undesired effects with aliskiren, compared with ramipril) [Duprez et al 2010] In summary, in light of new knowledge on RAS components, the approach to high blood pressure treatment continues developing encouragingly. Among all available agents, those inhibiting the RAS show clear pathogenic and pharmacokinetic advantages, as well as an excellent tolerability profile.…”
Section: Tolerability and Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the AGELESS study, aliskiren therapy was associated with a lesser incidence of adverse effects compared with ramipril (70% less undesired effects with aliskiren, compared with ramipril) [Duprez et al 2010] In summary, in light of new knowledge on RAS components, the approach to high blood pressure treatment continues developing encouragingly. Among all available agents, those inhibiting the RAS show clear pathogenic and pharmacokinetic advantages, as well as an excellent tolerability profile.…”
Section: Tolerability and Safetymentioning
confidence: 99%
“…For instance, the AGELESS Trial (Aliskiren for Geriatric Lowering of Systolic Hypertension) showed that aliskiren (either as monotherapy or combined with hydrochloro-thiazide) is more effective than ramipril at reducing systolic and diastolic blood pressure in patients older than 65 years with systolic hypertension [Duprez et al 2010].…”
Section: Effectiveness By Gender and Agementioning
confidence: 99%
“…Two good-quality RCTs compared the DRI aliskiren at a maximum dose of 300 mg to the ACE inhibitor ramipril at a maximum dose of 10 mg. [11][12][13] In both studies, aliskiren produced a greater reduction in blood pressure at 12 weeks, with between-group blood pressure (SBP/ DBP) differences of −2.7/-1.6…”
Section: Comparisons With Direct Renin Inhibitorsmentioning
confidence: 99%
“…Thirty studies (11 new, including two evaluating a DRI) presented original results on either serum creatinine/ GFR, 13,19,22,28,33,43,59,72,82,87,91,92 proteinuria, 11,29,58,60,80,103 or both. 23,30,46,49,56,62,65,73,81,97,99,102 The ten new studies that described changes in creatinine or glomerular filtration rate did not consistently demonstrate differential effects with use of ACE inhibitors versus ARBs, nor did the two studies comparing a DRI with the ACE inhibitor ramipril; 11,13 these findings were similar to those from the 2007 report.…”
Section: Serum Creatinine Level Glomerular Filtration Rate and Protmentioning
confidence: 99%
See 1 more Smart Citation